Performance of the preterm prevention clinic at heart of England NHS Trust. (18th April 2012) - Karkhanis, P; Patni, S; Sunanda, G
Abstract : Introduction: Preterm birth remains the major cause of neonatal mortality, in developed countries, despite major improvements in neonatal care. Appropriate antenatal intervention helped in prolonging gestation and reducing mortality and morbidity. This study was organised to review the cases managed by the trust's Preterm Prevention Clinic (PPC) and audit its performance based on trust and RCOG guideline. Methodology: The study involved a retrospective case-note analysis of patients registered under the PPC from November 2007 to January 2009. Results: 105 patients were registered during this time period, with mean age=30.16 years (18-41) and mean BMI = 27.86kg/m2. The commonest reason for referral was previous preterm labour or mid-trimester loss (n=83). Of these, 60 referrals were made after one previous preterm delivery, 19 were after two and 12 after three or more previous preterm losses. All patients underwent serial transvaginal scan monitoring and infection screening between 16 and 28 weeks. The relevant management options were discussed. 25 patients underwent cervical cerclage, of which 18 received progesterone supplementation. 29 patients had progesterone alone. 66 patients delivered after 37 weeks with mean birth weight of 2511gm. 26 preterm babies were admitted to the neonatal unit and only 5 of these babies died from complications of prematurity. Through the PPC, we achieved a term delivery rate (>37 weeks) in 74%, 42% and 41% in those patients with previous one, two and three preterm deliveries, respectively. Conclusion: With counselling and appropriate patient selection for intervention, the PPC has successfully reduced prematurity related morbidity and mortality in our unit.